Corporate Social Responsibility (CSR) Sebagai Tanggung Jawab Sosial - Nurasiah Harahap (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
Every company or cooperation is obligatory to carry out social and environmental responsibility. Corporate Social Responsibility (CSR) is regulated in Article 1 paragraph 3 of Law no. 40 of 2007 on Limited Liability Company which reads: "Social and environmental responsibility is the Company's commitment to play a role in sustainable economic development in order to improve the quality of life and environment that is beneficial for its own feelings, the local community and the community at large". About the obligatory of business, CSR is further regulated in Article 74 of the Law of Limited Liability Company and Government Regulation no. 47 of 2012 on Corporate Social Responsibility and Environment. Keywords: Limited Company, Social Responsibility